On the Integration of Core Socialist Values in the Teaching of International Politics - Wang, Baisong (IJRDO- Journal of Educational Research, 2020)
The integration of core socialist values in the teaching of international politics can not only improve the effectiveness of classroom teaching, but also enhance students’ cultural self-confidence and patriotic feeling. This paper emphatically discusses the importance, basic concepts and key points of core socialist values in international politics.